Analysis of the Effect of Green Banking, Corporate Social Responsibility, Ultimate Ownership on Bank Performance with Good Corporate Governance as a Moderating Variable - Allie, Riviera; Sudibijo, Yvonne Augustine (Technium Sustainability, 2024)
The purpose of this study was to determine the relationship between green banking, corporate social responsibility, ultimate ownership of bank performance with good corporate governance as a moderating variable. This research is quantitative research with panel data regression analysis techniques. The data used in this study are 17 commercial banks in Indonesia from 2020-2022. This study proves that the four hypotheses built show a positive and significant relationship. Green banking, corporate social responsibility, ultimate ownership have a positive and significant effect on bank performance. Then good corporate governance is also proven to be an amplifier of the relationship between green banking and bank performance. This study found a relationship between green banking and bank performance through indicators of the ability to earn net profit. This study uses data from 17 banks that have sustainability development reports in the 2020-2022 timeframe. This study also analyzes the role of good corporate governance in moderating the relationship between green banking and bank performance.